The effect of low vision rehabilitation on the quality of life and caregiver burden of low vision patients – a randomized trial - Chunling Cai; Yuwei Shuai; Gonghui Li (BMC Ophthalmology)
Abstract Background The quality of life for low vision patients is a comprehensive concept that involves multiple aspects, including physical, psychological, and social aspects. Visual impairment is an important factor in the decline of patients' quality of life. The purpose of this study is to investigate the impact and feasibility of carrying out low vision rehabilitation nursing on the quality of life and nursing burden of low vision patients. Methods Select 18 low vision patients who received treatment at a tertiary ophthalmic hospital in Shantou City and randomly divide them into an experimental group and a control group. The control group received routine low vision health education, while the experimental group received intervention measures based on low vision rehabilitation nursing plans. A questionnaire survey was conducted on two groups of study subjects and their caregivers using the Low Vision Quality of Life Questionnaire, General Self-Efficacy Scale, and Zarit Burden Interview before intervention, at week 4 after intervention, and at week 8 after intervention. The scores of each scale in the experimental group and the control group were statistically analyzed. Result The quality of life and self-efficacy scores of the experimental group patients were higher than those of the control group in the 4th and 8th week after intervention; The caregiver burden of the experimental group patients was lower than that of the control group caregivers in the 4th and 8th weeks after intervention. Conclusion Implement a low vision rehabilitation nursing plan, provide rehabilitation intervention and support to low vision patients, help patients find new ways to adapt to low vision conditions, and improve their quality of life. Low vision rehabilitation nursing interventions not only enable patients to regain the ability to independently complete daily activities, but also improve their self-efficacy, help rebuild confidence, and reduce the caregiving burden on their caregivers.